DINAMIKA PEMIKIRAN SANTRI: STUDI ATAS PENGARUH KEPEMIMPINAN DI PONDOK PESANTREN WAHID HASYIM CONDONGCATUR DEPOK SLEMAN (1998-2005) - Danar Widiyanta (LPPM UNY, 2008)
This research aims at exploring the dynamic of thinking of the santri (students) in PP Wahid Hasyim due to the influence of leadership. This research observes the role of a leader which in fact is really influencing the members of pesantren. In addition, this research also observes the interesting phenomenon, the dynamic of thinking showing progress in socio-religion thought which is basically beyond the tradition of pesantren which is salaf in nature. The result of this research shows that the role of leader is so significant. It can be seen from the existence of dynamic of thinking after the leadership of K.H. Jalal Suyuti. This dynamic is marked by the transformation of religion thought, from textual to contextual thinking (based on methodology) which is implemented by using book leading santri to think methodologically in facing problems of socio-religion.